357Infant pacifier sanitization and risk of food allergy: the Barwon Infant Study. (2nd September 2021) - Soriano, Victoria; Koplin, Jennifer; Forrester, Mike; Peters, Rachel; O'Hely, Martin; Dharmage, Shyamali; Wright, Rosemary; Ranganathan, Sarath; Burgner, David; Thompson, Kristie; Dwyer, Terence; Vuillermin, Peter; et al.
Abstract: Background: Environmental microbial exposure and human gut microbiota play a role in development of the immune system and susceptibility to food allergy. Pacifier use has been inconsistently associated with allergy, but the association between sanitization and food allergy is unknown. We investigated the association between infant pacifier use, with a consideration of sanitization, and food allergy at age 1 in the Barwon Infant Study (BIS). Methods: Questionnaire data were collected prospectively from pregnant mothers from the Barwon region of south-east Australia at baseline and at infant ages 1, 6, and 12 months. Pacifier sanitization was defined as the joint exposure of a pacifier and cleaning methods (antiseptic, mouth, tap water, boiling). Challenge-proven food allergy was determined at age 1. Results: Any pacifier use at 6 months was associated with food allergy (aOR, 1.94; 95% CI, 1.04-3.61), but not at other ages. This overall association was driven by the joint exposure pacifier-antiseptic use (aOR, 5.90; 95% CI, 2.18-15.97) compared to no pacifier use. Among pacifier users, pacifier-antiseptic was still associated with food allergy (aOR, 3.88; 95% CI, 1.55-9.72) when compared to pacifier-no antiseptic use. Further, increased use of pacifier-antiseptic at 0, 1 or 2 interviews over the first 6 months was associated with higher food allergy risk (ptrend =0.005). Conclusions: Joint exposure to antiseptics and pacifiers at 6 months increased the odds of food allergy, showing a trend with increased use over time. Key messages: This is the first report of pacifiers used with antiseptic being positively associated with challenge-proven food allergy.